Epitome of a good state: Exploring niche visible features of Malaysia / Mohd Rozaimy Ridzuan, Noor Amira Syazwani Abd Rahman and Wan Sumayyah Syahidah Wan Mohamad - Ridzuan, Mohd Rozaimy; Abd Rahman, Noor Amira Syazwani; Wan Mohamad, Wan Sumayyah Syahidah (Universiti Teknologi MARA Cawangan Pahang, 2021)
After more than 50 years of independence, many successes have been achieved, which enable Malaysia to become a role model for other countries. Two decades of Mahathir's leadership have resulted in Malaysia becoming more internationally recognised as a model of stable, multicultural and developing country with a relatively impressive economy. Hence, this paper attempts to acknowledge and explore several visible features that makes Malaysia a country to be embraced and respected. Specifically, this study aims to find out why other countries see Malaysia as their role model in specific areas or fields. Methodologically, this study utilizes a content analysis of the primary sources. The findings of the study would be beneficial in contributing to the existing body of knowledge.